If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q + 14 = 8(q + t) Reorder the terms: 14 + q = 8(q + t) 14 + q = (q * 8 + t * 8) 14 + q = (8q + 8t) Solving 14 + q = 8q + 8t Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-8q' to each side of the equation. 14 + q + -8q = 8q + -8q + 8t Combine like terms: q + -8q = -7q 14 + -7q = 8q + -8q + 8t Combine like terms: 8q + -8q = 0 14 + -7q = 0 + 8t 14 + -7q = 8t Add '-14' to each side of the equation. 14 + -14 + -7q = -14 + 8t Combine like terms: 14 + -14 = 0 0 + -7q = -14 + 8t -7q = -14 + 8t Divide each side by '-7'. q = 2 + -1.142857143t Simplifying q = 2 + -1.142857143t
| 0.5x-6=8 | | 8x-4x+7=1 | | 9x-75=6x-12 | | 5(3p+2)-2(4p-3)= | | 3x-1=8x | | ax-2x=a+2 | | 6x^2=7y | | c+2/4=3 | | 20x+6y=y | | 5d+13=2d-5 | | -54=6p-30 | | X-5-.10x=12+.5x | | 2x+5x=7Y+2 | | (X+4)(5x-6)=0 | | kx^2+12+k=0 | | x+45=56 | | -r=-12 | | 2(6-x)=-2(4-x) | | 9(x-3)=2(2x+9) | | x^4+2x^3-3x^2-36x=0 | | 6*(4-x)+6x=24 | | 32-5x=20-3x | | x-1+12=7x-25 | | 4x-6=5x-6 | | x+0.833(x)=7791.56 | | 3x^3+x=4x^2 | | 3x-2(6x-3)=42 | | 53+2x=18-3x | | 149-6x=6x+7 | | 7y+3x=20 | | 38-3x=23 | | 3(2x+5)=-3(-3x-2) |